Amblyomma yucumense n. sp (Acari: Ixodidae), a parasite of wild mammals in Southern Brazil - Krawczak, Felipe S.; Martins, Thiago F.; Oliveira, Caroline S.; Binder, Lina C.; Costa, Francisco B.; Nunes, Pablo H. [UNESP]; Gregori, Fabio; Labruna, Marcelo B. (Oxford Univ Press Inc, 2015)
During 2013-2014, adult ticks were collected on the vegetation and subadult ticks were collected from small mammals [Didelphis aurita Wied-Neuwied, Sooretamys angouya (Fischer), Euryoryzomys russatus (Wagner), Akodon montensis Thomas, Oxymycterus judex Thomas] in an Atlantic rainforest reserve in southern Brazil. Analyses of the external morphology of the adult ticks revealed that they represent a new species, Amblyomma yucumense n. sp. Partial 16S rRNA sequences generated from males, females, and nymphs were identical to each other and closest (95% identity) to corresponding sequences of Amblyomma dubitatum Neumann. A. yucumense is morphologically and genetically closest related to A. dubitatum. Dorsally, male of these species can be separated by major longitudinal pale orange stripes associated with a pseudoscutum indicated by a pale stripe in A. yucumense, in contrast to pale creamy longitudinal stripes and absence of pseudoscutum in A. dubitatum. Ventrally, male coxal I spurs are separated by a space narrower than external spur width in A. yucumense, and wider than external spur width in A. dubitatum. Females of the two species can be separated by coxal I spurs, longer in A. yucumense than in A. dubitatum. In addition, the adult capitulum and ventral idiosoma of A. yucumense are generally dark brown colored, while A. dubitatum is yellowish or light brown colored. The nymph of A. yucumense differs from A. dubitatum by the scutal cervical groove length, slightly shorter in the former species. Currently, A. yucumense is restricted to southern Brazil.
Keywords: Amblyomma; New species; Description; Brazil